2011
DOI: 10.1007/s11306-011-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of urinary organic acids in respiratory chain deficiencies in children

Abstract: Metabolomic analysis of the urinary organic acids from 39 selected children with defined respiratory chain deficiencies (RCDs) was performed using untargeted gas chromatography-mass spectrometry, revealing the presence of 255 endogenous and 46 exogenous substances. Variable reduction identified 92 variables from the endogenous substances, which could be analysed by univariate and multivariate statistical methods. Using these methods, no characteristic organic acid biomarker profile could be defined of practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 67 publications
0
54
0
1
Order By: Relevance
“…Many of these organic acids are highly specific markers used to detect neonatal inborn errors of metabolism (Pitt et al 2002). Organic acid analysis also proved valuable in our recent study that revealed a global profile of perturbations related to disorders of mitochondrial components (Reinecke et al 2011). These few examples indicate that organic acids are appropriate components of the metabolome for investigating the possible metabolic effects of HIV infection.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Many of these organic acids are highly specific markers used to detect neonatal inborn errors of metabolism (Pitt et al 2002). Organic acid analysis also proved valuable in our recent study that revealed a global profile of perturbations related to disorders of mitochondrial components (Reinecke et al 2011). These few examples indicate that organic acids are appropriate components of the metabolome for investigating the possible metabolic effects of HIV infection.…”
Section: Introductionmentioning
confidence: 95%
“…Organic acids were isolated from HIV-and HIV+ serum by solvent extraction prior to GC-MS analysis according to a published protocol (Reinecke et al 2011). All reagents used for organic acid extraction were from Merck (Darmstadt, Germany) unless otherwise stated.…”
Section: Organic Acid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these two values must be CS. Any deficient marker (CII or CIV) was excluded for interpretation and if both CII and CIV were deficient, only CS was used for identification b Clinical profile includes: Aid auto-immune disorder, BE behavior and emotional abnormalities, Car cardiac involvement, CNS central nervous system involvement, DD developmental delay, DR developmental regression, Dys dysmorphism (minor and major), E epilepsy, End endocrine abnormalities, ENT sensori-neural deafness, Eye vision involvement, G gastro-intestinal tract involvement, L liver involvement, M muscle involvement, PNS peripheral neuropathy, R renal involvement, S skeletal involvement, Skin Skin involvement c MDC score Mitochondrial Disease Score (Wolf and Smeitink 2002) described before (Smuts et al 2010, Reinecke et al 2012 were included in the RCD group and the patients with clinical features of a RCD but RC enzyme levels within the reference range were categorised to the CC group. Table 1 summarizes the characteristics of the selected experimental groups.…”
Section: Sample Selection and Experimental Groupsmentioning
confidence: 99%
“…However, the control group used in this and related studies (Reinecke et al 2012) consisted of clinically healthy patients. This signature can therefore not be applied to limit the inclusion of false positive patients (i.e.…”
Section: Introductionmentioning
confidence: 99%